Development of constrained tamoxifen mimics and their antiproliferative properties against breast cancer cells. Issue 3 (1st February 2015) - Archana, Sivakumar; Geesala, Ramasatyaveni; Rao, Narasimha B.; Satpati, Suresh; Puroshottam, Giridhar; Panasa, Akhila; Dixit, Anshuman; Das, Amitava; Srivastava, Ajay Kumar
Graphical abstract